The role of gut microbiome in personalized medicine and chronic disease prevention - Kumar Sahu, Deepak; Srinivasa Rao, Varri (Journal of Neonatal Surgery, 2025)
The gut microbiome, a diverse community of microorganisms residing in the human gastrointestinal tract, plays a pivotal role in maintaining health and preventing diseases. Emerging research highlights the significant influence of the gut microbiota on chronic conditions such as diabetes, cardiovascular diseases, and inflammatory disorders. Personalized medicine has increasingly focused on microbiome modulation through diet, probiotics, and prebiotics to tailor treatments specific to an individual's microbiome composition. This approach has demonstrated promising results in mitigating disease progression and improving therapeutic outcomes. This paper reviews the gut microbiome's role in personalized medicine, with an emphasis on its application in chronic disease prevention and treatment strategies. Key challenges and future opportunities for microbiome-based interventions are also discussed, underscoring its transformative potential in healthcare.